PENGENALAN KULTUR TEKNIS DAN SIMBIOSIS ANTAR TANAMAN DENGAN KONSEP REFUGIA KEPADA PETANI DI KECAMATAN OBA TENGAH KOTA TIDORE KEPULAUAN - Rima Melati; Abdullah W. Jabid; Abdul Rahmat Mandea (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Farmers in Central Oba District independently cultivate horticultural crops as their primary source of income; however, their approach to preventing and controlling plant pests and diseases relies solely on chemical pesticides, leading to unsustainable agricultural practices. This activity aimed to provide information on cultivation techniques based on a mutually beneficial symbiotic relationship between crops and pests—specifically through the planting of refugia crops. The objective was pursued through training sessions and field visits involving farmers and staff representatives from the North Maluku Province Parent Seed Center. The results indicate that the farmers have gained knowledge and an understanding of the benefits of refugia plants. Ongoing farmer assistance—specifically through demonstrations on the propagation and planting of refugia—is necessary to encourage farmers to implement these practices in their own fields.